Optimizing low-speed DTC performance for three-phase induction motors with sector rotation strategy - Sabri, Nurul Syahada Muhamad; Tarusan, Siti Azura Ahmad; Zawawi, Syed Abrar S. A.; Jidin, Auzani; Sutikno, Tole (International Journal of Power Electronics and Drive Systems (IJPEDS), 2025)
This paper proposes a modification to the direct torque control (DTC) strategy for induction motors, focusing on improving flux performance at lower speeds. The method employs a sector rotation strategy to address stator flux droop, which occurs in conventional DTC due to the impact of stator resistance at low speed becoming more significant. This constrains the ability of the flux vector to be tangential to the voltage vector in the default sector. Consequently, an improper flux locus leads to distortion of the phase currents which disrupts precise control of torque. The proposed approach dynamically adjusts the sector angle to mitigate flux droop while maintaining the simplicity and original structure of DTC. The new sector rotation strategy is validated through simulations in MATLAB/Simulink to demonstrate the effectiveness of the proposed method in reducing stator flux droop. These findings have potential applications in the industrial sector and electric vehicles, where stable motor operation and smoother driving performance at low speeds are crucial for precise control operation.